Sign in

Sign up

Answered by **christoph**

First, multiply the first equation by 2.That turns the first equation into:6x - 2y = 18That way it can easily be added to the second equation:6x - 2y = 16x + 2y = 5---------------7x = 21==========As you can see, the y disappeared, which was the objective of this operation.Now the equations can be solved easily:7x = 21x = 3Insert x=3 in the original equation:3*3 - y = 89 - y = 89 = 8 + yy = 1So the result is:x = 3y = 1

Answered by **D3xt3R**

Now we can multiply the first row by 2 and add to the second row.themnow we can replace the value in the first row.

Didn't find the right answer?

Use site search If you are not satisfied with the answer. Or browse Mathematics category to find out more.

Ask Your Question

Questions without answers